DNA Methylation Biomarkers Predict Objective Responses to PD-1/PD-L1 Inhibition Blockade - Xue, Gang; Cui, Ze-Jia; Zhou, Xiong-Hui; Zhu, Yue-Xing; Chen, Ying; Liang, Feng-Ji; Tang, Da-Nian; Huang, Bing-Yang; Zhang, Hong-Yu; Hu, Zhi-Huang; Yuan, Xi-Yu; Xiong, Jianghui (Frontiers in Genetics, 2019)
Immune checkpoint inhibitor (ICI) treatment could bring long-lasting clinical benefits to patients with metastatic cancer. However, only a small proportion of patients respond to PD-1/PD-L1 blockade, so predictive biomarkers are needed. Here, based on DNA methylation profiles and the objective response rates (ORRs) of PD-1/PD-L1 inhibition therapy, we identified 269 CpG sites and developed an initial CpG-based model by Lasso to predict ORRs. Notably, as measured by the area under the receiver operating characteristic curve (AUC), our model can produce better performance (AUC = 0.92) than both a model based on tumor mutational burden (TMB) (AUC = 0.77) and a previously reported TMB model (AUC = 0.71). In addition, most CpGs also have additional synergies with TMB, which can achieve a higher prediction accuracy when joined with TMB. Furthermore, we identified CpGs that are associated with TMB at the individual level. DNA methylation modules defined by protein networks, KEGG pathways and ligand-receptor gene pairs are also associated with ORRs. This method suggested novel immuno-oncology targets that might be beneficial when combined with PD-1/PD-L1 blockade. Thus, DNA methylation studies might hold great potential for individualized PD1/PD-L1 blockade or combinatory therap